2021
DOI: 10.1128/msystems.01153-20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Concrete Reflect Its Composite Nature and Change with Weathering

Abstract: Concrete is an extreme but common environment and is home to microbial communities adapted to alkaline, saline, and oligotrophic conditions. Microbes inside the concrete that makes up buildings or roads have received little attention despite their ubiquity and capacity to interact with the concrete. Because concrete is a composite of materials which have their own microbial communities, we hypothesized that the microbial communities of concrete reflect those of the concrete components and that these communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 127 publications
(172 reference statements)
2
19
2
Order By: Relevance
“…These microbes encode pathways that potentially allow them to mitigate the primary selective pressures in concrete, including heavy metal tolerance and a variety of osmotic stress responses. This contrasts with our previous work in much younger concrete (< 3 years old), which used 16S amplicon sequencing to characterize a microbial community composed primarily of generalist, sometimes oligotrophic bacteria, and no detectable Archaea 1 .…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…These microbes encode pathways that potentially allow them to mitigate the primary selective pressures in concrete, including heavy metal tolerance and a variety of osmotic stress responses. This contrasts with our previous work in much younger concrete (< 3 years old), which used 16S amplicon sequencing to characterize a microbial community composed primarily of generalist, sometimes oligotrophic bacteria, and no detectable Archaea 1 .…”
Section: Discussioncontrasting
confidence: 71%
“…However, it may take years for extreme environments to be colonized by microbes capable of thriving there, and even longer for them to reach detectable levels. We previously found that in the early months of concrete weathering, microbial communities in concrete resembled those of the precursor materials used in the concrete mix 1 . Over two years, the diversity of bacteria decreased and became more similar to the microbial communities associated with the large aggregates and cement powder, potentially indicating that these components share characteristics with concrete.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Unlike indoor surfaces, outdoor surfaces are often exposed to uncontrolled and harsh environmental conditions, such as intense ultraviolet light, fluctuating temperature, desiccation, and poor nutrient supply. These conditions and stressors not only induce esthetic deterioration of the surfaces (e.g., corrosion), but also threaten the survival of microbial residents [ 19 ]. However, some of the microbes can adapt to and survive such stresses by a variety of strategies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%